On the Thermal Conductivity of Gold Nanoparticle Colloids - Shalkevich, Natallia; Escher, Werner; Bürgi, Thomas; Michel, Bruno; Si-Ahmed, Lynda; Poulikakos, Dimos (Langmuir, 2010)
Nanofluids (colloidal suspensions of nanoparticles) have been reported to display significantly enhanced thermal conductivities relative to those of conventional heat transfer fluids, also at low concentrations well below 1% per volume (Putnam, S. A., et at. J. Appl. Phys. 2006, 99, 084308; Liu, M.-S. L., et al. Int. J. Heat Mass Transfer. 2006, 49; Patel, H. E., et al. Appl. Phys. Lett. 2003, 83, 2931−2933). The purpose of this paper is to evaluate the effect of the particle size, concentration, stabilization method and particle clustering on the thermal conductivity of gold nanofluids. We synthesized spherical gold nanoparticles of different size (from 2 to 45 nm) and prepared stable gold colloids in the range of volume fraction of 0.00025−1%. The colloids were inspected by UV−visible spectroscopy, transmission electron microscope (TEM) and dynamic light scattering (DLS). The thermal conductivity has been measured by the transient hot-wire method (THW) and the steady state parallel plate method (GAP method). Despite a significant search in parameter space no significant anomalous enhancement of thermal conductivity was observed. The highest enhancement in thermal conductivity is 1.4% for 40 nm sized gold particles stabilized by EGMUDE (triethyleneglycolmono-11-mercaptoundecylether) and suspended in water with a particle-concentration of 0.11 vol%.